Implementasi Artificial Intelligence pada Mata Pelajaran IPAS dengan Mengintegrasikan Nilai-nilai Keagamaan pada Kelas V di MI Nurul Huda Jepara - Shofianur, Eva; Ahsani, Eva Luthfi Fakhru (SENTRI: Jurnal Riset Ilmiah, 2025)
This research aims to describe the implementation of Artificial Intelligence (AI) in the IPAS subject by integrating religious values in Class V at Madrasah Ibtidaiyah (MI) Nurul Huda Jepara. This research is a qualitative descriptive study, with teachers and students of Class V at MI Nurul Huda Jepara as subjects. Data collection techniques in this research used observation sheets for teachers and students, as well as interviews. Qualitative data analysis focused on an in-depth understanding through data from interviews, observations, and literature, with research steps including data reduction, data presentation, and conclusion drawing and verification. The results of this research show that the implementation of Artificial Intelligence (AI) in the form of Canva-based animated videos in IPAS subject by integrating religious values can provide optimal understanding related to the learning material "Technology for Life" and understanding related to religious values such as aqidah education values, akhlak education values, and ibadah education values, which obtained an average score of 93.3%. This is also proven through teacher observation sheets and student observation sheets, which respectively obtained average scores of 96.25% and 95%. Thus, animated videos are very effective when used as learning support rather than just using lecture and storytelling methods.